Recommendations for Clinical Decision-making in Children with Type 1 Diabetes and Celiac Disease: Type 1 Diabetes and Celiac Disease Joint Working Group Report - ERTEM ŞAHİNOĞLU, DENİZ (My University, 2021)
It is well-known that in children with type 1 diabetes (T1D), the frequency of celiac disease (CD) is increased due to unclear mechanisms including autoimmune injury as well as shared genetic predisposition. Although histopathologic examination is gold standard, avoiding unnecessary endoscopy is crucial. Therefore, from the perspective of the clinicians and patients' families, the diagnosis of celiac disease remains challenging. With these in mind, a joint working group (Type 1 Diabetes and Celiac Disease Joint Working Group) was gathered, with the aim of reporting institutional data, as well as the current recommendations of international organizations, in order to provide a framework for clinicians. Several controversial issues were discussed: For CD screening in children with T1D, regardless of age, it is recommended to measure tTG-IgA (tissue transglutaminase-Immunoglobulin A) and/or endomysial (EMA-IgA) antibody due to their high sensitivity and specificity. However, the decision-making process based on tTG-IgA titer in children with T1D is still debated, since tTG-IgA titers may fluctuate in children with T1D. Moreover, seronegativity may occur spontaneously. The authors' own data showed that most of the cases who have biopsy-proven CD had tTG-IgA levels 7-10 times above the upper limit. The decision of endoscopy based solely on tTG-IgA levels should be avoided, except in cases where tTG-IgA levels are 7 times and above the upper limit. A closer collaboration should be built between divisions of pediatric endocrinology and gastroenterology in terms of screening, diagnosis and follow-up of children with T1D and suspicious CD.
Keywords: Children; anti-tissue transglutaminase-IgA; Celiac disease; Type 1 Diabetes